Quick-hardening early-strength ultra-high performance concrete and preparation method thereof
By using sulfuricate cement and other optimized raw materials, the problems of slow development of ultra -high -performance concrete in the early stage of ultra -high -performance concrete are solved, and efficient construction and reinforcement repair are realized, and the durability and cracking performance of concrete are improved.
Patent Information
- Application Number
- CN202410975076.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-01-24
AI Technical Summary
The early strength of existing ultra-high performance concrete is slowly developing, and it is difficult to carry out on-site construction and reinforcement and repair.
Using sulphoaluminate cement as the main cementing material, combined with raw materials such as Portland cement, silica fume, steel fiber, polycarboxylate superplasticizer and sodium sulfate, through optimized proportions and specific mixing and curing processes, it can significantly improve Early strength of concrete.
The concrete has reached a higher intensity in a short period of time, shortened the construction cycle, reduced the difficulty of reinforcement and repair, improved durability and crack resistance, and was suitable for complex and changeable construction environment and long -term use needs.
Smart Images

Figure CN119349966A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and specifically relates to a fast-hardening and early-strength ultra-high performance concrete and a preparation method thereof. Background Art
[0002] With the rapid development of China's economy, the number of concrete buildings and bridges has increased dramatically. Due to the continuous increase in traffic volume, a large number of concrete pavements and bridges have suffered varying degrees of damage, which has reduced the service life of concrete buildings and greatly affected building and driving safety. The emergence of repair materials has extended the service life of concrete buildings. Therefore, the development and research of some advanced rapid repair materials with excellent repair performance is beneficial to both building safety and social economy, and is of great significance.
[0003] At present, repair materials can be mainly divided into three types: inorganic cement repair materials, organic repair materials and organic-inorganic composite repair materials. For example, CN114538862A discloses a concrete defect repair material prepared with epoxy resin, xylene and lead powder as raw materials. Although it can effectively improve the strength of concrete, the organic repair material has a large curing shrinkage rate, and cracks caused by shrinkage are prone to appear at the bonding interface, affecting the repair effect. For example, CN110041033A discloses a road surface rapid repair material with ordinary silicate cement plus calcium formate, triisopropanolamine, polyvinyl alcohol and other admixtures. Although it has the advantages of convenient construction and good bonding effect with old concrete, it has low mechanical strength in the later stage, which is not conducive to the long-term service of the project. In view of the shortcomings of the above repair materials, it is urgent to develop a new rapid repair material.
[0004] Ultra-high performance concrete is a new generation of materials designed based on the most compact packing theory, with excellent durability and outstanding mechanical properties. Ultra-high performance concrete has broad application prospects in the fields of long-span bridge engineering, marine engineering, national defense engineering, etc. with its excellent performance. However, ordinary ultra-high performance concrete has a long setting time and obvious self-shrinkage, which has an adverse effect on the mechanical properties and durability after repair, and seriously limits the application of ultra-high performance concrete in rapid repair. Therefore, the research and development of fast-hardening early-strength ultra-high performance concrete is not only conducive to making up for the shortcomings of existing repair materials, but also can broaden the application of ultra-high performance concrete in engineering. For example, CN111233405A discloses a fast-hardening ultra-high performance concrete and a preparation method thereof, which makes silicate cement, fast-hardening agent, retarder, mineral powder, fly ash, silica fume, sand, admixture, steel fiber, and water stir evenly in a certain proportion to obtain fast-hardening ultra-high performance concrete. The fast-hardening ultra-high performance concrete of the invention overcomes the shortcomings of existing fast-hardening materials such as obvious cracks, short service life and poor durability, but silicate cement requires a large amount of heat energy during the production process and produces a large amount of CO2, which puts pressure on the environment. Compared with silicate cement, sulphoaluminate cement requires lower firing temperature, emits less CO2, and has the characteristics of fast coagulation and hardening, high early strength and fast development. Therefore, the present invention provides a method for preparing sulphoaluminate cement-based fast-hardening early-strength ultra-high performance concrete. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a fast-hardening and early-strengthening ultra-high performance concrete and a preparation method thereof, so as to solve the problems of slow early strength development and great difficulty in on-site construction and reinforcement and repair of ultra-high performance concrete in the prior art.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is a fast-hardening and early-strengthening ultra-high performance concrete, the preparation raw materials of which mainly include, by weight: 925-1005 parts of cementitious materials, 250-290 parts of coarse aggregate, 900-960 parts of fine aggregate, 145-170 parts of steel fibers, 40-60 parts of water reducer, 140-170 parts of water and 1-7 parts of early strength agent.
[0007] In a preferred embodiment, the cementitious material includes sulphoaluminate cement, silicate cement and silica fume, wherein, by weight, sulphoaluminate cement accounts for 80% of the total amount of cementitious materials, silicate cement accounts for 9% of the total amount of cementitious materials, and silica fume accounts for 11% of the total amount of cementitious materials.
[0008] In a preferred embodiment, the SiO2 content of the silica ash is higher than 94%.
[0009] In a preferred embodiment, the water reducer is a polycarboxylate water reducer; and the early strength agent is sodium sulfate.
[0010] In a preferred embodiment, the steel fiber is a straight steel fiber.
[0011] In a preferred embodiment, the coarse aggregate is crushed stone with a particle size of 5-10 mm; the fine aggregate is quartz sand with a particle size of 0.125-1.18 mm.
[0012] A method for preparing a fast-hardening, early-strength ultra-high performance concrete is a method for preparing any one of the fast-hardening, early-strength ultra-high performance concrete described above, comprising the following steps: Step 1: Weigh sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, steel fiber, water reducer, sodium sulfate and water according to the weight ratio of each component; Step 2: Evenly mix the weighed water and water reducing agent to obtain mixed solution A; Step 3: Place sulphoaluminate cement, silica fume, quartz sand and sodium sulfate in a concrete mixer and stir until mixed evenly. Add 2 / 3 of mixed liquid A first, then add the remaining mixed liquid A after stirring, then add crushed stone and continue stirring, finally add steel fiber and stir until mixed evenly. Put into a mold for natural curing to obtain fast-hardening and early-strength ultra-high performance concrete.
[0013] In a preferred solution, the concrete is prepared by a mixing method, and the feeding sequence and mixing time of each raw material are strictly controlled during the preparation process to ensure stable performance of the concrete.
[0014] In a preferred embodiment, during the preparation of the concrete, the raw materials need to be pre-treated, including screening, washing and drying steps to improve the purity and uniformity of the concrete; in addition, the key raw materials sulphoaluminate cement and silica fume need to be quality tested to ensure that they meet the preparation requirements.
[0015] In the preferred solution, during the preparation process of the concrete, the stirring time and stirring speed need to be controlled to ensure that the various components of the concrete are fully mixed and evenly distributed; at the same time, the quality of the concrete after stirring needs to be tested, including indicators such as compressive strength and flexural strength, to ensure that it meets the design requirements.
[0016] The invention provides a fast-hardening, early-strength ultra-high performance concrete and a preparation method thereof, which have the following beneficial effects: 1. The present invention solves the problems of slow early strength development and great difficulty in on-site construction and reinforcement repair of ultra-high performance concrete in the prior art; 2. The present invention significantly improves the early strength of concrete, shortens the construction period, reduces the difficulty of reinforcement and repair, and provides strong technical support for the sustainable development of the construction industry by optimizing the raw material ratio, introducing high-performance additives, and adopting a unique preparation process; 3. The present invention optimizes the concrete mix ratio, introduces a high-efficiency water reducing agent and an early strength agent, and combines specific mixing and curing processes to achieve a higher strength of concrete in a shorter time. At the same time, the method also takes environmental protection and cost-effectiveness into consideration, providing a new approach for the application of ultra-high performance concrete. 4. The present invention also introduces fiber-reinforced materials, which further improve the mechanical properties and durability of concrete, making it more suitable for complex and changeable construction environments and long-term use requirements. The successful development of this technology has injected new vitality into the development of the construction field; 5. The ultra-high performance concrete prepared by using sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, steel fiber, sodium sulfate and water as raw materials has the characteristics of rapid hardening and early strength, and its 1h compressive strength reaches 33.5MPa, and 1d compressive strength reaches 76.4MPa, which can solve the problem of slow early strength development of ultra-high performance concrete at present, and the later strength does not shrink (56d compressive strength is 130.1MPa); 6. The present invention uses sulphoaluminate cement as the main cementitious material. Sulphoaluminate cement-based ultra-high performance concrete can quickly reach high strength in the early stage of the concrete hardening process while maintaining low porosity and high density, thereby significantly improving the durability of the repair material. In addition, compared with traditional silicate cement, the production process of sulphoaluminate cement has a lower clinker burning temperature and less CO2 released during the burning process, which meets the requirements of energy conservation and emission reduction; 7. The present invention also adds an appropriate amount of mineral admixtures and high-efficiency water reducing agent, and further optimizes the mechanical properties, durability and working performance of ultra-high performance concrete by accurately controlling the proportion of each component and the preparation process, making it more suitable for various complex engineering repair needs; 8. The addition of silica fume in the present invention can optimize the particle gradation and make the structure more compact, and silica fume can promote the hydration reaction and improve the mechanical properties of concrete; 9. The present invention uses sodium sulfate as an early strength agent. The addition of sodium sulfate causes a large amount of sulfate ions to exist in the system, which accelerates the reaction rate of calcium sulfoaluminate, generates ettringite and aluminum gel, and forms a dense crystalline structure network with calcium silicate hydrate, making the structure more dense; 10. The present invention adopts a multi-mineral admixture technology, such as silica fume, quartz sand, etc. These admixtures react with cement hydration products to produce a secondary hydration reaction, and the generated gel fills the internal pores of the concrete, making the concrete more compact and improving the durability of the concrete; 11. The fast-hardening, early-strength ultra-high performance concrete prepared by the present invention has high early strength (1h compressive strength 33.5MPa, 1d compressive strength 76.4MPa), no shrinkage in later strength (56d compressive strength 130.1MPa), can be used for rapid repair, emergency repair and construction projects, and is easy to maintain and environmentally friendly; 12. The fast-hardening, early-strengthening ultra-high performance concrete prepared by the present invention adopts special additives and precise mix ratio design, so that the concrete can reach a higher strength in a short time after pouring; this concrete not only hardens quickly, but also has excellent compressive and tensile properties, and is widely used in projects such as bridges and tunnels that require rapid repair and reinforcement.
[0017] 13. The preparation process of the present invention is simple, the production cost is low, and it is environmentally friendly and meets the requirements of sustainable development. Practical applications show that the rapid-hardening and early-strengthening ultra-high performance concrete of the present invention has significant engineering and social benefits. 14. The fast-hardening, early-strengthening ultra-high performance concrete prepared by the present invention also has excellent durability and crack resistance, and can maintain stable performance under extreme environments, providing reliable material guarantees for various projects; at the same time, the concrete also has excellent construction performance and is easy to process and shape. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention will be further described below in conjunction with the accompanying drawings and implementation examples: Figure 1 The microstructure of the rapid-hardening and early-strengthening ultra-high performance concrete mixed with 3 parts of sodium sulfate at 1 hour. Figure 2 The microstructure of the rapid-hardening and early-strengthening ultra-high performance concrete added with 3 parts of sodium sulfate at 3d age; Figure 3 The microstructure of the rapid-hardening and early-strengthening ultra-high performance concrete added with 3 parts of sodium sulfate at 28 days old; Figure 4 This is the microstructure of the rapid-hardening and early-strengthening ultra-high performance concrete added with 3 parts of sodium sulfate at 56 days old. DETAILED DESCRIPTION
[0019] The embodiments of the present invention are further described below in conjunction with the accompanying drawings: Example 1 A fast-hardening and early-strengthening ultra-high performance concrete, the preparation raw materials of which mainly include, by weight: 925-1005 parts of cementitious materials, 250-290 parts of coarse aggregates, 900-960 parts of fine aggregates, 145-170 parts of steel fibers, 40-60 parts of water reducing agents, 140-170 parts of water and 1-7 parts of early strength agents.
[0020] In this embodiment, the cementitious material includes sulphoaluminate cement, silicate cement and silica fume. By weight, sulphoaluminate cement accounts for 80% of the total amount of cementitious materials, silicate cement accounts for 9% of the total amount of cementitious materials, and silica fume accounts for 11% of the total amount of cementitious materials.
[0021] Furthermore, the SiO2 content of the silica ash is higher than 94%.
[0022] Furthermore, the water reducer is a polycarboxylate water reducer; and the early strength agent is sodium sulfate.
[0023] Furthermore, the steel fiber is a straight steel fiber.
[0024] Furthermore, the coarse aggregate is crushed stone with a particle size of 5-10 mm; the fine aggregate is quartz sand with a particle size of 0.125-1.18 mm.
[0025] In the specific preparation, a method for preparing a fast-hardening and early-strength ultra-high performance concrete is a method for preparing any one of the fast-hardening and early-strength ultra-high performance concrete described above, comprising the following steps: Step 1: Weigh sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, steel fiber, water reducer, sodium sulfate and water according to the weight ratio of each component; Step 2: Evenly mix the weighed water and water reducing agent to obtain mixed solution A; Step 3: Place sulphoaluminate cement, silica fume, quartz sand and sodium sulfate in a concrete mixer and stir until mixed evenly. Add 2 / 3 of mixed liquid A first, then add the remaining mixed liquid A after stirring, then add crushed stone and continue stirring, finally add steel fiber and stir until mixed evenly. Put into a mold for natural curing to obtain fast-hardening and early-strength ultra-high performance concrete.
[0026] Furthermore, the concrete is prepared by a mixing method, and during the preparation process, the feeding sequence and mixing time of each raw material are strictly controlled to ensure stable performance of the concrete.
[0027] Furthermore, during the preparation process of the concrete, the raw materials need to be pre-treated, including screening, cleaning and drying steps to improve the purity and uniformity of the concrete; in addition, the key raw materials sulphoaluminate cement and silica fume need to be quality tested to ensure that they meet the preparation requirements.
[0028] Furthermore, during the preparation of the concrete, the mixing time and mixing speed need to be controlled to ensure that the various components of the concrete are fully mixed and evenly distributed; at the same time, the quality of the mixed concrete needs to be tested, including indicators such as compressive strength and flexural strength, to ensure that it meets the design requirements.
[0029] Example 2 In another preferred embodiment, on the basis of the above-mentioned embodiment 1, the main raw materials of the fast-hardening and early-strength ultra-high performance concrete described in this embodiment include, by weight: 771 parts of sulphoaluminate cement, 86 parts of silicate cement, 108 parts of silica fume, 272 parts of coarse aggregate, 933 parts of fine aggregate, 157 parts of steel fiber, 48 parts of water reducer, 154 parts of water, and 3 parts of early strength agent.
[0030] In this embodiment, the coarse aggregate is crushed stone with a particle size of 5-10 mm; the fine aggregate is quartz sand with a particle size of 0.125-1.18 mm; the steel fiber is a straight steel fiber; the water reducer is a polycarboxylate water reducer; the early strength agent is sodium sulfate; and the SiO2 content of the silica fume is higher than 94%.
[0031] Weigh sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, straight steel fiber, polycarboxylate water reducer, sodium sulfate and water according to the weight ratio of the above components; evenly mix the weighed water and polycarboxylate water reducer to obtain a mixed solution A; place sulphoaluminate cement, silica fume, quartz sand and sodium sulfate in a concrete mixer and stir for 1 to 2 minutes. After the mixture is evenly mixed, first add 2 / 3 of the mixed solution A, then stir for 1 to 2 minutes, then add the remaining mixed solution A, stir for 3 to 4 minutes, then add crushed stone and stir for 2 to 3 minutes, finally add straight steel fiber and stir until the mixture is evenly mixed, put into a mold for natural curing, and obtain fast-hardening and early-strength ultra-high performance concrete.
[0032] In this embodiment, a scanning electron microscope is used to perform phase analysis on fast-hardening, early-strength ultra-high performance concrete of different ages; Figures 1 to 4 They are SEM images of hydration samples of the rapid-hardening, early-strength ultra-high performance concrete of this embodiment after curing for 1h, 3d, 28d and 56d respectively; Figure 1 As shown in the figure, after hydration for 1 hour, granular CSH, fine needle-like AFt, flocculent AH3, flaky CH and unhydrated spherical silica fume particles can be observed in the microstructure of the hydrated sample; fine needle-like AFt, flaky CH and silica fume particles are filled between CSH and AH3, and the cement paste structure is relatively dense; Figure 2 As shown in the figure, after hydration for 3 days, needle-shaped AFt, network-like CSH, massive CH, floc-like AH3 and spherical silica fume particles with CSH gel layer can be observed in the microstructure of the hydrated sample; massive CH, needle-shaped AFt and silica fume particles are filled between CSH and AH3, and the cement paste is more dense; the results show that after hydration for 3 days, the hydration degree of cement particles deepens, the number of hydration products increases, the development becomes better, and the connection between CSH and AH3 becomes denser; some silica fume particles participate in hydration, which plays a physical filling role and increases the content of CSH. Figure 3 As shown in Figure 2, after hydration for 28 days, long rod-shaped AFt, block-shaped CSH, block-shaped CH and elliptical AH3 can be observed in the microstructure of the hydrated sample; long rod-shaped Aft, block-shaped CH and elliptical AH3 are embedded in CSH, and the cement paste is more dense; Figure 4As shown in the figure, at 56 days of hydration, long columnar AFt, blocky CSH, blocky CH and irregular AH3 can be observed in the microstructure of the hydrated sample; long columnar AFt, blocky CH and irregular AH3 are embedded in CSH, and the cement paste is more compact. The results show that at 56 days of hydration, the degree of hydration of cement particles is extremely high, the number of hydration products is large and well developed, and the connection between CSH and AH3 is tight.
[0033] Example 3 In another preferred embodiment, on the basis of the above-mentioned embodiment 1, the main raw materials of the fast-hardening and early-strength ultra-high performance concrete described in this embodiment include, by weight: 771 parts of sulphoaluminate cement, 86 parts of silicate cement, 108 parts of silica fume, 272 parts of coarse aggregate, 933 parts of fine aggregate, 157 parts of steel fiber, 48 parts of water reducer, 154 parts of water, and 6 parts of early strength agent.
[0034] In this embodiment, the coarse aggregate is crushed stone with a particle size of 5-10 mm; the fine aggregate is quartz sand with a particle size of 0.125-1.18 mm; the steel fiber is a straight steel fiber; the water reducer is a polycarboxylic acid water reducer; the early strength agent is sodium sulfate; and the SiO2 content of the silica fume is higher than 94%.
[0035] Weigh sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, straight steel fiber, polycarboxylate water reducer, sodium sulfate and water according to the weight ratio of the above components; evenly mix the weighed water and polycarboxylate water reducer to obtain a mixed solution A; place sulphoaluminate cement, silica fume, quartz sand and sodium sulfate in a concrete mixer and stir for 1 to 2 minutes. After the mixture is evenly mixed, first add 2 / 3 of the mixed solution A, then stir for 1 to 2 minutes, then add the remaining mixed solution A, stir for 3 to 4 minutes, then add crushed stone and stir for 2 to 3 minutes, finally add straight steel fiber and stir until the mixture is evenly mixed, put into a mold for natural curing, and obtain fast-hardening and early-strength ultra-high performance concrete.
[0036] Example 4 In another preferred embodiment, based on the above-mentioned embodiment 1, the main raw materials of the fast-hardening and early-strength ultra-high performance concrete described in this embodiment include, by weight: 771 parts of sulphoaluminate cement, 86 parts of silicate cement, 108 parts of silica fume, 272 parts of coarse aggregate, 933 parts of fine aggregate, 157 parts of steel fiber, 48 parts of water reducer, and 154 parts of water.
[0037] In this embodiment, the coarse aggregate is crushed stone with a particle size of 5-10 mm; the fine aggregate is quartz sand with a particle size of 0.125-1.18 mm; the steel fiber is a straight steel fiber; the water reducer is a polycarboxylic acid high water reducer; and the SiO2 content of the silica fume is higher than 94%.
[0038] Weigh sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, straight steel fiber, polycarboxylate water reducer and water according to the weight ratio of the above components; evenly mix the weighed water and polycarboxylate water reducer to obtain a mixed solution A; place sulphoaluminate cement, silicate cement, silica fume and quartz sand in a concrete mixer and stir for 1 to 2 minutes. After the mixture is evenly mixed, first add 2 / 3 of the mixed solution A, then stir for 1 to 2 minutes, then add the remaining mixed solution A, stir for 3 to 4 minutes, then add crushed stone and stir for 2 to 3 minutes, finally add the straight steel fiber and stir until the mixture is evenly mixed, put into a mold for natural curing, and obtain ultra-high performance concrete.
[0039] Example 5 In another preferred embodiment, on the basis of the above-mentioned embodiment 1, the main raw materials of the fast-hardening and early-strength ultra-high performance concrete described in this embodiment include, by weight: 771 parts of sulphoaluminate cement, 86 parts of silicate cement, 108 parts of silica fume, 272 parts of coarse aggregate, 933 parts of fine aggregate, 157 parts of steel fiber, 48 parts of water reducer, 154 parts of water, and 9 parts of early strength agent.
[0040] In this embodiment, the coarse aggregate is crushed stone with a particle size of 5-10 mm; the fine aggregate is quartz sand with a particle size of 0.125-1.18 mm; the steel fiber is a straight steel fiber; the water reducer is a polycarboxylic acid high-performance water reducer; the early strength agent is sodium sulfate; and the SiO2 content of the silica fume is higher than 94%.
[0041] Weigh sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, straight steel fiber, polycarboxylic acid high-performance water reducer, sodium sulfate and water according to the weight ratio of the above components; evenly mix the weighed water and polycarboxylic acid high-performance water reducer to obtain a mixed solution A; place sulphoaluminate cement, silica fume, quartz sand and sodium sulfate in a concrete mixer and stir for 1 to 2 minutes. After the mixture is evenly mixed, first add 2 / 3 of the mixed solution A, then stir for 1 to 2 minutes, then add the remaining mixed solution A, stir for 3 to 4 minutes, then add crushed stone and stir for 2 to 3 minutes, finally add straight steel fiber and stir until the mixture is evenly mixed, put into a mold for natural curing, and obtain fast-hardening and early-strength ultra-high performance concrete.
[0042] According to the "Ultra-High Performance Concrete Test Method Standard" T / CECS 864-2021, the physical and mechanical properties tests of rapid hardening and early strength ultra-high performance concrete of Examples 2 to 5 were carried out, and the results are shown in Table 1.
[0043] Table 1 Comparison of physical and mechanical properties of fast-hardening and early-strength ultra-high performance concrete in Examples 2 to 5
[0044] It can be seen from Table 1 that the compressive and flexural strengths of the fast-hardening and early-strength ultra-high performance concretes of Examples 2 to 3 of the present invention are greater than 30 MPa and 4 MPa, respectively, when cured at room temperature for 1 hour. The compressive and flexural strengths of Example 4 at 1 hour are relatively low, only about 70% of the compressive and flexural strengths of Example 2, which shows that the fast-hardening and early-strength ultra-high performance concrete of the present invention has ultra-high mechanical strength at an early stage; the addition of sodium sulfate can shorten the setting time of ultra-high performance concrete and improve the early strength of ultra-high performance concrete, but with the increase of the sodium sulfate content, it can be seen from the performance indicators of Example 5 that the working performance of the ultra-high performance concrete is inhibited, and the effect of improving the strength is also weakened, so the addition amount of sodium sulfate should not be too much; in summary, the fast-hardening and early-strength ultra-high performance concrete of the present invention has ultra-high strength at an early stage, and the strength is steadily improved within 28 days, and the strength does not shrink in the later stage.
[0045] In a preferred embodiment, the cementitious material includes sulphoaluminate cement, silica fume and silica ash, wherein, by weight, sulphoaluminate cement accounts for 80% of the total amount of cementitious materials, silica fume accounts for 9% of the total amount of cementitious materials, and silica fume accounts for 11% of the total amount of cementitious materials; with the above arrangement, the high strength and rapid hardening characteristics of sulphoaluminate cement provide superior mechanical properties and early strength for concrete, silicate cement enhances the durability of concrete, and the addition of silica fume further improves the impermeability and wear resistance of concrete.
[0046] In a preferred embodiment, the SiO2 content of the silica fume is higher than 94%. With the above arrangement, the high SiO2 content of the silica fume ensures its excellent chemical stability and mechanical strength, so that the final product has higher durability and reliability. In addition, the particle size distribution of the silica fume is also carefully controlled to ensure its uniform dispersion in concrete and excellent filling effect.
[0047] In a preferred embodiment, the water reducer is a polycarboxylate water reducer; the early strength agent is sodium sulfate; the above arrangement can effectively improve the fluidity and strength of concrete during the concrete preparation process, ensuring smooth construction; the polycarboxylate water reducer can significantly reduce the water-cement ratio of concrete, improve the impermeability and durability of concrete; and the sodium sulfate early strength agent can accelerate the hardening process of concrete and improve the early strength.
[0048] In a preferred embodiment, the steel fiber is a straight steel fiber; in the above configuration, the addition of the straight steel fiber can significantly improve the crack resistance and impact resistance of the concrete, so that the concrete can better maintain its structural integrity when subjected to external forces. At the same time, the addition of the straight steel fiber can also improve the wear resistance and durability of the concrete and extend its service life.
[0049] In the preferred solution, the coarse aggregate is crushed stone with a particle size of 5 to 10 mm; the fine aggregate is quartz sand with a particle size of 0.125 to 1.18 mm; the above arrangement ensures the stability and strength of the concrete structure; in addition, an appropriate amount of cement and high-efficiency water reducing agent are added to improve the compressive strength and working performance of the concrete; this mix ratio not only ensures the durability of the concrete, but also optimizes the construction efficiency.
[0050] In the preferred scheme, the concrete is prepared by a mixing method, and the feeding sequence and mixing time of each raw material are strictly controlled during the preparation process to ensure the stable performance of the concrete; the above settings not only improve the strength of the concrete, but also greatly reduce the generation of bubbles and voids, thereby improving the density and durability of the concrete; in addition, by optimizing the proportion of raw materials and the mixing process, the crack resistance and weather resistance of the concrete are also significantly improved.
[0051] In the preferred scheme, during the preparation process of the concrete, the raw materials need to be pretreated, including screening, washing and drying steps to improve the purity and uniformity of the concrete; in addition, the key raw materials, sulphoaluminate cement and silica fume, need to be quality tested to ensure that they meet the preparation requirements; the above settings enable the concrete to maintain high stability and reliability during the preparation process; during the mixing process, the uniformity and strength of the concrete are further ensured by precisely controlling the mixing time and speed; in addition, the maintenance and cleaning of the mixing equipment are also strictly managed to ensure the preparation quality of the concrete.
[0052] In the preferred solution, during the preparation of the concrete, the stirring time and stirring speed need to be controlled to ensure that the various components of the concrete are fully mixed and evenly distributed; at the same time, the quality of the concrete after stirring needs to be tested, including indicators such as compressive strength and flexural strength, to ensure that it meets the design requirements; the above settings not only improve the quality stability of the concrete, but also effectively prevent the occurrence of quality problems such as cracking and crazing of the concrete during production and use, thereby ensuring the smooth progress of the project construction; in addition, optimizing the mixing parameters can also reduce production costs and improve production efficiency.
[0053] In summary, the fast-hardening and early-strengthening ultra-high performance concrete and its preparation method proposed in the present invention solve the problems of slow early strength development and great difficulty in on-site construction and reinforcement and repair of ultra-high performance concrete in the prior art; by optimizing the raw material ratio, introducing high-performance additives, and adopting a unique preparation process, the early strength of concrete is significantly improved, the construction period is shortened, and the difficulty of reinforcement and repair is reduced, providing strong technical support for the sustainable development of the construction industry; by optimizing the concrete ratio, introducing high-efficiency water reducing agent and early strength agent, combined with specific mixing and curing processes, the concrete can achieve higher strength in a shorter time; at the same time, the method also takes environmental protection and cost-effectiveness into consideration, providing a new way for the application of ultra-high performance concrete; the present invention also introduces fiber-reinforced materials to further improve the mechanical properties and durability of concrete, so that It is more suitable for complex and changeable construction environments and long-term use needs. The successful development of this technology has injected new vitality into the development of the construction field. The invention has proved its stability and reliability in practical applications through a large number of experimental verifications and engineering practices, and provides a solid theoretical basis and practical guidance for the application of ultra-high performance concrete in major projects such as bridges, tunnels, and high-rise buildings. The research and development results of the invention are of great significance for improving the technical level of the construction industry and promoting the innovative development of materials science. In the future, we will continue to deepen research, optimize preparation processes, expand application areas, and contribute more to the sustainable development of society. At the same time, we also look forward to exploring the potential of ultra-high performance concrete in building energy conservation, environmental protection, and intelligence with partners inside and outside the industry, and jointly promote the construction industry to develop in a greener, more efficient, and intelligent direction.
Claims
1. A fast-hardening, early-strength ultra-high performance concrete, characterized in that: The raw materials for its preparation mainly include, by weight: 925-1005 parts of cementitious materials, 250-290 parts of coarse aggregate, 900-960 parts of fine aggregate, 145-170 parts of steel fiber, 40-60 parts of water reducing agent, 140-170 parts of water and 1-7 parts of early strength agent.
2. The rapid hardening and early strength ultra-high performance concrete according to claim 1, characterized in that: The cementitious material comprises sulphoaluminate cement, silicate cement and silica fume, wherein, by weight, sulphoaluminate cement accounts for 80% of the total amount of the cementitious material, silicate cement accounts for 9% of the total amount of the cementitious material, and silica fume accounts for 11% of the total amount of the cementitious material.
3. The rapid hardening and early strength ultra-high performance concrete according to claim 2, characterized in that: The SiO2 content of the silica fume is higher than 94%.
4. The rapid hardening and early strength ultra-high performance concrete according to claim 3, characterized in that: The water reducing agent is a polycarboxylate water reducing agent; and the early strength agent is sodium sulfate.
5. The rapid hardening and early strength ultra-high performance concrete according to claim 4, characterized in that: The steel fiber is a straight steel fiber.
6. The rapid hardening and early strength ultra-high performance concrete according to claim 5, characterized in that: The coarse aggregate is crushed stone with a particle size of 5-10 mm; the fine aggregate is quartz sand with a particle size of 0.125-1.18 mm.
7. A method for preparing fast-hardening, early-strength ultra-high performance concrete, characterized in that: A method for preparing a rapid-hardening, early-strength ultra-high performance concrete according to any one of claims 1 to 6, the method comprising the following steps: Step 1: Weigh sulphoaluminate cement, silicate cement, silica fume, crushed stone, quartz sand, steel fiber, water reducer, sodium sulfate and water according to the weight ratio of each component; Step 2: Evenly mix the weighed water and water reducing agent to obtain mixed solution A; Step 3: Place sulphoaluminate cement, silica fume, quartz sand and sodium sulfate in a concrete mixer and stir until mixed evenly. Add 2 / 3 of mixed liquid A first, then add the remaining mixed liquid A after stirring, then add crushed stone and continue stirring, finally add steel fiber and stir until mixed evenly. Put into a mold for natural curing to obtain fast-hardening and early-strength ultra-high performance concrete.
8. The method for preparing a rapid-hardening, early-strength ultra-high performance concrete according to claim 7, characterized in that: The concrete is prepared by a mixing method, and during the preparation process, the feeding sequence and mixing time of each raw material are strictly controlled to ensure stable performance of the concrete.
9. The method for preparing a rapid-hardening, early-strength ultra-high performance concrete according to claim 8, characterized in that: During the preparation of the concrete, the raw materials need to be pre-treated, including screening, cleaning and drying steps to improve the purity and uniformity of the concrete; the key raw materials, sulphoaluminate cement and silica fume, also need to be quality tested to ensure that they meet the preparation requirements.
10. The method for preparing a rapid-hardening, early-strength ultra-high performance concrete according to claim 9, characterized in that: During the preparation of the concrete, the mixing time and mixing speed must be controlled to ensure that the various components of the concrete are fully mixed and evenly distributed; at the same time, the quality of the mixed concrete must be tested, including indicators such as compressive strength and flexural strength, to ensure that it meets the design requirements.
Citation Information
Patent Citations
Cold region cement concrete pavement quick repair material and preparation method thereof
CN110041033A
Quick-hardening ultra-high performance concrete and preparation method thereof
CN111233405A
Concrete defect repairing material
CN114538862A
Cited By
Mine supporting material interface reinforcing agent, its preparation method and application
CN122916503A